Productivity and efficiency in food industries in Iran - Afrooz, Ahmad (2012)
Economists, managers and those involved in economic planning all over the world are familiar with the term ‘productivity’ as it is the central concept in planning strategies for nation building. It is a concept with far-reaching impacts, especially in the areas of national economy and social well-being. The importance of productivity cannot be overly stated, as it affects all humanity, be it at the national, industrial or individual levels. Efficiency and productivity studies can be useful to diagnose problems and make recommendations based on their empirical work and their review of economic theories of industrial productions. Many stakeholders, policy makers, managers, and owners of agribusinesses are concerned with the results established in these efficiency and productivity studies. In line with these facts, efficiency and productivity analyses are important in this modern era of rapidly changing technology and increasing input costs. Furthermore, efficiency analysis which is aimed at studying factors affecting productivity will guide policy-makers in the planning and management of their national economy. The food industry in Iran is widely recognized as a 'sunrise industry', with a huge potential for uplifting the agricultural economy and creating large-scale processed food manufacturing and food-chain facilities which may result in the generation of employment and export earnings. The industry also possesses enormous significance for Iran’s development due to the vital linkages and synergies that it promotes between the two pillars of the economy, namely industry and agriculture. In addition, the food industry is also one of the largest industries in Iran. In fact, the industry is ranked as the top industry in terms of its provision of employment (18 percent) and the number of manufacturers (20 percent). In spite of the importance of the industry, there are several problems faced by the manufacturers and also within the food industry. While the food industry of Iran is labour-intensive, most of the problems are related to the workforce and factors affecting their productivity. On the other hand, over the last two decades, the government has encouraged privatization for the expansion of agro-industries and food industry. Unfortunately, the position of food industry, in comparison with other industries in terms of labor productivity and total factor productivity, remains to be in the dark to the authorities up until now. Considering the above mentioned problems and also the importance of the food industry due to the policies of the precedence of the Non-Oil Exports in Foreign Trade, Response to Nutrition Requirements of the Population and the Prevention of Wastage, this study examines the determinants of labour productivity, efficiency and technical changes in Iran’s food industry from 1995-2006. Thus, in order to achieve the objectives of this study, the parametric approaches are applied. Meanwhile, the Stochastic frontier approach is utilized to measure efficiency and determinants of inefficiency. Cob-Douglass production is also applied to estimate technical changes. This research should fill several gaps in the literature on the determinants of productivity and efficiency. Many stakeholders, policy makers, managers, and owners of agribusinesses are interested in the results established in various efficiency and productivity studies. In line with the above statement, the efficiency and productivity analyses are therefore, important in the current era of rapidly changing technology and increasing input costs. Even more so, the efficiency analysis is aimed at studying the factors affecting productivity that would help guide policymakers in aspects like planning and management. Hence, a comparison of efficiency and productivity in the private and public sectors of food industry will guide policymakers and authorities for better planning in the future. Briefly, this study has attempted to comprehensively investigate the determinants of efficiency in the entire food industry, including both the private sector and government sectors of the food industries separately. Likewise, the levels of efficiency in the aforementioned areas have also been estimated. Next, the productivity and efficiency of the private and public sectors of the food industry are compared. Finally, the total factor of productivity growth is calculated and compared with that of all the other industries as a whole. This study applies the Cobb-Dougla production function of industry to examine the determinants of productivity and total factor of the productivity growth. Also, the Stochastic Frontier Analysis is utilized in measuring the total efficiency, both in the private and public food industry sectors. The results of this study show that the labor productivity and the total factor of productivity of the food industry are lower than those of the global industrial average over the same period. Moreover, an estimation of the technical change in the public and private sectors of the food industry is respectively 0.064 and 0.16 percent over the same period. Meanwhile, determinants such as the specialization of the workers, their education level and skills, contain the most effects on the labor productivity in both sectors in the food industry. In particular, their education level, skills, and specialization have contributed to the differences in Iran’s productivity of food industry. The most important factor is found to be the employee’s specialization in this industry. An estimation of efficiency shows that Iran’s food industry is only 74% technically efficient. Comparisons of private and public sectors of food industry have revealed that unlike the implications of classic theories, in which the private food industry sectors are always better than the public sector, the labor productivity and total factor of the productivity of the food industry are higher in the public sectors of the food industry than those of its private sectors over the same period. The technical efficiency in both sectors, however, is notably close to each other. Some of the important implications of this study are as follows: (1) The government should facilitate in creating training workshops for both the private and the public sectors; (2) The private sectors should attempt to invest in the education of its workers and employ more specialized workers, and the utilization of new machineries and new technology by private manufacturers should also be increased; (3) The Government should attempt to develop the field of food industries in universities; (4) Manufacturers should also attempt to manage the ratio of their workers with regards to their abilities, skills, and wages; and (5) Manufacturers should consider insuring their workers.